2020
DOI: 10.1002/adma.201907818
|View full text |Cite
|
Sign up to set email alerts
|

2D Transition Metal Dichalcogenides: Design, Modulation, and Challenges in Electrocatalysis

Abstract: Hydrogen has been deemed as an ideal substitute fuel to fossil energy because of its renewability and the highest energy density among all chemical fuels. One of the most economical, ecofriendly, and high‐performance ways of hydrogen production is electrochemical water splitting. Recently, 2D transition metal dichalcogenides (also known as 2D TMDs) showed their utilization potentiality as cost‐effective hydrogen evolution reaction (HER) catalysts in water electrolysis. Herein, recent representative research ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
285
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 377 publications
(286 citation statements)
references
References 250 publications
(311 reference statements)
1
285
0
Order By: Relevance
“…All the positions of S 2p 1/2 , S 2p 3/2 peak were in accordance with the previous literature ( Figure 2d) [24]. However, we observed that the peak of S 2-2p3/2 have 0.05 eV shift toward low blinding energy, which indicated that S became easier to obtain electrons after forming heterostructure [45] and also confirmed peak of Mo 6+ 3d5/2 (232.63 eV) and Mo 6+ 3d3/2 (235.73 eV) were further enhanced because of the conservation of gain and loss electrons [5]. In summary, formation of heterostructure caused the increase of O-vacancies on the defective WO 3 surface and the generation of Mo-O bond by oxygen incorporation into MoS 2 layer.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…All the positions of S 2p 1/2 , S 2p 3/2 peak were in accordance with the previous literature ( Figure 2d) [24]. However, we observed that the peak of S 2-2p3/2 have 0.05 eV shift toward low blinding energy, which indicated that S became easier to obtain electrons after forming heterostructure [45] and also confirmed peak of Mo 6+ 3d5/2 (232.63 eV) and Mo 6+ 3d3/2 (235.73 eV) were further enhanced because of the conservation of gain and loss electrons [5]. In summary, formation of heterostructure caused the increase of O-vacancies on the defective WO 3 surface and the generation of Mo-O bond by oxygen incorporation into MoS 2 layer.…”
Section: Resultssupporting
confidence: 85%
“…Electrocatalysts water-splitting product hydrogen is reproducible and clean energy [1][2][3]. The development of platinum (Pt)-free electrocatalysts is a crucial problem to improve the generally efficiency for hydrogen evolution reaction (HER), especially when facing resources shortage and energy crisis [4][5][6]. Newly, two-dimensional (2D) transition metal chalcogenides have always been mentioned, such as molybdenum disulfide (MoS 2 ) [7,8], tungsten oxide (WO 3 ) [9,10], molybdenum selenide (MoSe 2 ) [11,12] and can demonstrated to clarify the mechanism for HER in strong acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, electrical conductivity is another essential requirement for an advanced electrocatalyst. [6,7,12,31] However, the intrinsic low conductivity of ReS 2 impedes its application in HER. [31,32] Synergizing or coupling with conductive substrates is a common method to considerably enhance the conductivity of TMDCs.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical water‐splitting through hydrogen evolution reaction (HER) has been considered as a sustainable way for producing hydrogen, a clean and renewable energy source. [ 1–7 ] Platinum (Pt) has been widely recognized as the best HER catalyst, but subject to its high cost and limited storage. Therefore, to replace Pt, many efforts have been devoted to electrocatalysts based on non‐noble metals such as transition metal complexes, oxides, phosphide, carbides, and transition metal dichalcogenides (TMDCs).…”
Section: Introductionmentioning
confidence: 99%